Artecnología para la prevención de la violencia en Comunidad : un proceso psicoeducativo desde el arte y la tecnología para la prevención de la violencia, con niños y niñas que asisten el Parque La Libertad - Segura Umaña, Gabriela (2019)
The present graduation project had as a general objective, through a methodology inspired by the Reggio Emilia approach, which involves a process of learning through self-construction and social construction in the children population; and the incorporation of the use of different manifestations of art and of technologies as approach tools, generate a process psychoeducational that will facilitate reflection on the prevention of violence in the community context of boys and girls who attend the Centro Infantil y Juvenil del La Libertad Park (PLL) in San José, Costa Rica. For the development of the project, the following specific objectives were established: to identify the different manifestations of violence present in the community context from the perspective of children, to problematize with them alternatives of healthy coexistence and resolution of conflicts through artistic expressions and technological, and develop strategies for the prevention of violence at the community level. The present project was also based on conceptual references from Lev Vygotsky's Social Constructivism and Popular Education developed by Paulo Freire, since from the work that was desired to be carried out with the boys and girls of the community, on the subject of manifestations of violence and prevention alternatives, it was necessary to understand the space of social interaction in which the problem to be dealt with is inserted; The role played by the individual in acquiring knowledge and skills through experience is also relevant to the project. In this way, the gaze and listening were directed towards the participating boys and girls as actors who build their knowledge and communicate it through concrete experiences; also rescuing the development of creativity and freedom of action, which allowed putting into practice, making use of artistic expressions such as drawing, sculpture, theater and technologies viii such as photography, video and the development of apps, innovative strategies to address the phenomenon of violence and its prevention. Among the main results obtained, the following are framed: the boys and girls were able to identify at least three manifestations of direct violence and three manifestations of structural violence in the community context, and from that identification they were able to problematize alternatives of action before said manifestations. Once they problematized such alternatives, they were able to develop violence prevention strategies at the community level using artistic expressions and technologies. These results contributed to achieving the general objective of the project, which revolved around generating a process of reflection on the prevention of violence. Therefore, it was possible to facilitate and accompany actions aimed at the denaturalization of violence and the implementation of healthy coexistence alternatives that influence the construction of a culture of peace. The Artecnology space, in addition to being formulated as a space in which this process of reflection should be generated, should also be constituted as a space in itself for non-violence. Therefore, based on activities aimed at the establishment and exercise of healthy interpersonal relationships, the participants were able to adopt new forms of relationship throughout the work sessions that were based on participation, dialogue, and recognition of each other. , the development of common projects, and democracy as an experience and experience within the psychoeducational process. Regarding the methodology used, the lived process demonstrated that the union between tools from art and technologies, articulated from a psychosocial and psychoeducational approach to the phenomenon of violence, facilitates and enhances the structuring and appropriation of new ways of understanding and acting. in the social reality of each of the participants